Vulvar itch - Tkaczuk-Włach, Joanna; Sobstyl, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2010)
Vulvar itch is a common symptom and distressing problem. Puritius is an unpleasant sensation inducting the desire to scratch. Diagnosis is made by history, clinical investigation, skin and vaginal patch testing or skin biopsy. Acute vulvar purities is usually caused by infection or contact dermatitis. In chronic purities inflammatory dermatoses and malignancies must be taken into consideration. The key success factors are: identification of the etiological agent, avoiding skin irritation and breaking the cycle of itching and scratching.